Influence of Freezing Treatment on the Thermal Runaway Characteristics of Lithium-Ion Batteries. Issue 1 (November 2020) - Wweng, J; Ouyang, D X; Chen, MY; Ding, C; Wang, J
Abstract: Owing to increasing applications of lithium-ion batteries (LIBs), it is worth investigating the thermal runaway (TR) behaviors of LIBs under extreme conditions such as flash freezing, which has been proposed as a feasible way for LIB transportation or storage. In this study, a series of experiments was conducted to explore and compare the TR behaviors of batteries with and without freezing treatment. According to the results, the batteries after freezing treatment exhibited a faster temperature rise, and the onset time of TR ( t ) was shortened. For example, t was 277.2 s in the blank test, whereas for the battery after 72 h freezing, t was 250.2 s. Moreover, the microstructure comparison on the internal electrode materials after TR showed that freezing treatment aggravated the agglomeration and clustering of them. Additionally, we recommend storing LIBs with a lower state of charge (SOC) even in freezing or extreme-cold conditions.